Induction of Resistance in Bhendi Accessions against Whitefly, Bemisia tabaci (Gennadius) under Field Condition - Saraswathi, J. M.; Muthukumaran , N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Two bhendi accessions were screened for the induction of resistance by seed treatment with agriculturally beneficial microorganisms like Azospirillum, Phosphobacteria and K-solubilizer against whitefly, Bemisia tabaci (Genn.) at the Department of Entomology, Faculty of Agriculture, Annamalai University. Accession Salem Local along with Arka Anamika was screened with different agriculturally beneficial microorganisms under field condition. The nymphal population of whitefly was recorded during two (Rabi and Kharif) seasons of 2022. Among the treatments, the accession Salem Local treated with K- solubilizer recorded the lowest nymphal population followed by the treatment, Azospirillum + Phosphobacteria + K-solubilizer. Whereas the maximum nymphal population was observed in Arka Anamika treated with Azospirillum with the mean nymphal population of 3.32 and 3.65 in the Rabi and Kharif seasons respectively. Hence, the accessions following seed treatment that conferred resistance against whitefly were selected for breeding in order to develop whitefly resistant varieties.